Prevalence and influencing factors of healthy lifestyle among adult residents in Beijing city, 2017: a cross-sectional survey - Kai FANG; Aijuan MA; Zhong DONG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo understand the distribution characteristics of healthy lifestyles among adult residents in Beijing. MethodsUsing data from the surveillance of chronic diseases and their risk factors among adults in Beijing in 2017, a multistage stratified cluster random sampling method was used to select 13 240 permanent residents aged 18 - 79 in 16 districts of Beijing from August to December in 2017 for questionnaire surveys, physical examinations, and laboratory tests. The respondents' lifestyles were assessed using a comprehensive rating scale, with scores ranging from 0 to 6, indicating the degree of healthy lifestyle from low to high. The lifestyle factors and comprehensive lifestyle score distribution characteristics of the residents were analyzed, and lifestyle differences between residents in healthy and non-healthy communities were compared. ResultsAmong the 12 570 participants analyzed, the complex-weighted proportions of non-smokers, non-excessive alcohol drinkers, individuals with a healthy diet, individual with active physical activity, normal weight individuals, and those without central obesity were 77.0% (n = 9 413), 91.8% (n = 11 525), 46.0% (n = 5 532), 26.3% (n = 3 161), 36.7% (n = 4 751), and 36.0% (n = 4 847), respectively. The mean healthy lifestyle score was 3.14 ± 0.03 for all participants, and the highest proportion of participants (28.8%, n = 3 513) were scaled with a score of 3; the proportion of participants with a score of 6, indicating six components of a healthy lifestyle, was only 2.8% (n = 308). The results of univariate analysis showed that the individuals with the following characteristics were more likely to have a higher healthy lifestyle score: being female (odds ratio [OR] = 4.130, 95% confidence interval [95%CI]: 3.581 - 4.763), having a higher educational level (junior high school vs. elementary school and below: OR = 1.408, 95%CI: 1.204 - 1.646; college and above vs. elementary school and below OR = 2.067, 95%CI: 1.775 - 2.407), and living in healthy communities (OR = 1.181, 95%CI: 1.025 - 1.362); while compared to the younger individuals (18 - 39 years) and those living in urban areas, the middle-aged individuals (40 - 59 years) and those living in suburban areas were more likely to have lower scores, with the ORs (95%CI) of 0.806 (0.725 - 0.896) and 0.796 (0.671 - 0.943), respectively. Multivariate linear regression analysis revealed that after adjusting for other demographic and sociological factors, healthy lifestyle scores were higher among people living in healthy communities than those living in non-healthy communities (β = 0.107, 95%CI: 0.005 - 0.209), and the difference was statistically significant (P = 0.041).ConclusionThe prevalence of a healthy lifestyle, including physical activity, body weight, and waist circumference, among adults in Beijing is relatively low. In addition, the proportion of people who adhere to all six components of a healthy lifestyle remains disappointingly low. Furthermore, there are disparities in the adoption of healthy lifestyles by gender, age group, educational background, and residential area.